Consumer Perceptions and Decision-Making in the Non-Fungible Token - Helmi Ismail, Mohd Amirul; Zaibon, Syamsul Bahrin; Abdul Hamid, Mohd Noor; Mustajap, Siti Irna; Ismail, Adzrool Idzwan (SHPMedia Sdn Bhd, 2024)
This study investigates how consumer perceptions affect decision-making in the purchase of Non-Fungible Tokens (NFTs), providing a detailed analysis of the factors driving consumer behavior in this emerging market. Using a mixedmethods approach, this study conducted surveys and interviews with NFT purchasers to capture a comprehensive view of their decision-making processes. Our findings reveal that factors such as perceived value, trust in blockchain technology, and the influence of community engagement significantly impact purchasing intentions. These insights contribute to the existing literature by delineating specific consumer behaviors and motivations in the NFT space, highlighting the importance of community trust and perceived technological robustness. Additionally, the study offers practical implications for businesses in the NFT sector, suggesting that establishing strong, credible relationships within the NFT community, and staying abreast of technological advancements are pivotal strategies for maintaining a competitive advantage. By integrating with NFT communities and leaders, businesses can glean trends and collaborative opportunities, fostering innovation, and market leadership in the dynamic NFT landscape